CLINICAL OUTCOME OF INFANTS OF DIABETIC MOTHERS: A DESCRIPTIVE STUDY (The Research of Medical Science Review, 2024)
Objective: To evaluate the clinical outcomes of infants born to diabetic mothers (IDMs) in a tertiary care hospital in Bahawalpur, Pakistan.Study Design: This descriptive study explores the outcomes of neonates born to diabetic mothers in terms of common complications, including hypoglycemia, hypocalcemia, polycythemia, macrosomia, and hyperbilirubinemia. Place and Duration of Study: The study was conducted in the Neonatal Intensive Care Unit (NICU) of the Department of Pediatrics, Quaid-e-Azam Medical College/B.V. Hospital Bahawalpur, over six months after ethical approval.Methodology: A total of 100 neonates born to diabetic mothers (gestational or pre-gestational diabetes) were included through non-probability consecutive sampling. Data on maternal glycemic control, delivery details, and neonatal outcomes were recorded. Blood samples were taken to measure glucose, calcium, hematocrit, and bilirubin levels, and clinical outcomes were documented. Data were analyzed using SPSS v.25.Results: The mean gestational age of neonates was 37 ± 2.1 weeks, with 45% male and 55% female participants. Hypoglycemia was the most common complication (63.8%), followed by hyperbilirubinemia (57.4%), hypocalcemia (43%), polycythemia (35%), and macrosomia (15%). A significant association was found between maternal glycemic control and neonatal complications.Conclusion: Infants of diabetic mothers are at higher risk of metabolic and systemic complications. Early identification and management of these outcomes can reduce neonatal morbidity and improve prognosis.